THE TRAINING TO UTILIZE SOCIAL MEDIA TO INCREASE PRODUCTIVITY OF LOCAL ARTISTS IN EAST JAKARTA DURING COVID-19 PANDEMIC - Wininda Qusnul Khotimah; Dini Wahdiyati (Universitas Ahmad Dahlan, 2021)
The COVID-19 pandemic affects many sectors of life including the world of art, particularly for local artists. They no longer have a stage to work on. The restriction policies during the pandemic Covid-19 limit their existence. As a result, the local artists in East Jakarta need a way to stay creative and productive. The lack of work performed has an impact on the lack of income they get. Thus, the community service team is looking for a solution to this problem by providing education about the use of social media. The method from this community service is carried out by providing knowledge about the types, features, and use of social media. Then, provide training to create content from the work of these local East Jakarta artists. From this training, East Jakarta local artists have started to understand the types, features, and use of social media. Besides, they also started to create content to share on their social media